Directions state to use one or more properties to rewrite the expression as an expression that does not use parentheses. another question example is (a+5) + 23

## 7.(y.3) use one or more properties to rewrite without parentheses

Tutors, please sign in to answer this question.

# 1 Answer

if you're trying to rewrite 7*(y*3), then you just multiply 7 by 3y and you would get 21y

7*(y*3) = 7*(3*y) = (7*3)*y = 21y

## Comments

and for the other example question

(a+5)+23 = a+(5+23) = a+28

Comment